Clinical Characteristics of Febrile UTI First Developed Over 5 Years of Age - Roh, Da Eun; Suh, Hyo Rim; Min, So Yoon; Jo, Tae Kyoung; Baek, Hee Sun; Cho, Min Hyun (Childhood kidney diseases, 2017)
Purpose Febrile urinary tract infection (UTI) is one of the commonest bacterial infections in children. The purpose of this study is to investigate the clinical characteristics of the first episode of febrile UTI occurring in children over 5 years compared to those in infants younger than a year. Methods We retrospectively reviewed the medical records of 10 patients over 5 years, having febrile UTI, and 25 controls under 1 year. Clinical characteristics including symptoms at admission, the time interval between symptom onset and hospital visit and/or diagnosis, duration of fever, urinalysis, and other laboratory and imaging test results were compared between the two groups. Results Most patients in the control group showed only high fever at the time of presentation to the hospital. However, 60% of the case group had fever along with gastrointestinal (GI) symptoms such as abdominal and flank pain, vomiting, as well as relatively mild pyuria. The case group showed a longer duration between symptom onset and hospital visit and/or diagnosis. Conclusions Delay in diagnosis and initiation of treatment of UTI increases the risk of permanent renal scarring and associated complications. Therefore, early diagnosis and treatment of febrile UTI is vital for very young infants, as well as children considering that febrile UTI could be an important cause of febrile illness in children over 5 years.